2004
DOI: 10.1097/00126334-200401010-00008
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Positive Injection Drug Users Who Leave the Hospital Against Medical Advice

Abstract: Among HIV-positive patients with a history of injection drug use, the odds of leaving the hospital AMA were reduced for subjects who received inpatient methadone treatment, were of older age, or had social supports. Addiction treatment and interventions that enhance social supports in marginalized populations at risk for hospital discharge AMA should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 18 publications
6
99
3
Order By: Relevance
“…2 Patients who leave AMA are more likely to have poorer social supports, to abuse alcohol, heroin, and other substances, and often have weighty psychosocial or financial concerns. [12][13][14][15][16][17][18] They are also less likely to have an established relationship with a primary care physician. 19 Although studies have found that rates of discharge AMA are higher among some ethnic minorities, one recent study suggests that other patient variables, such as level of income and type of insurance, may be more closely related.…”
mentioning
confidence: 99%
“…2 Patients who leave AMA are more likely to have poorer social supports, to abuse alcohol, heroin, and other substances, and often have weighty psychosocial or financial concerns. [12][13][14][15][16][17][18] They are also less likely to have an established relationship with a primary care physician. 19 Although studies have found that rates of discharge AMA are higher among some ethnic minorities, one recent study suggests that other patient variables, such as level of income and type of insurance, may be more closely related.…”
mentioning
confidence: 99%
“…29,49,50 Available evidence suggests that opioid agonist therapy, when paired with referral to outpatient addiction services, may reduce discharge against medical advice and increase engagement in postdischarge addiction treatment. [51][52][53][54][55] One observational study of in patients with opioid use disorder showed that initiation of methadone during the hospital stay, coupled with linkage to an outpatient addiction program, led to a high rate (82%) of postdischarge follow-up. 54 A randomized controlled trial showed that inpatient initiation of buprenorphine and referral to an outpatient addiction provider led to significantly better rates of long-term treatment for opioid use disorder than inpatient detoxification alone (16.7% v. 3%, p = 0.007, at 6 months after the hospital stay).…”
Section: Is There Benefit To Inpatient Initiation Of Opioid Agonist Tmentioning
confidence: 99%
“…Consistent with the evidence identifying a complex drug use-income relationship, and given the difficulty of observing drug use, a number of studies have linked monthly SA disbursement to cyclical and substantial increases in the risk of experiencing drug-related harms, including accidental overdose (Otterstatter, Amlani, Guan, Richardson, & Buxton, 2016;Riddell & Riddell, 2006;Verheul, Singer, & Christenson, 1997;Zlotorzynska et al, 2014), hospitalizations (Dobkin & Puller, 2007;Halpern & Mechem, 2001;Maynard C, 2000), drug-induced psychiatric emergency department visits (Catalano & McConnell, 1999;Pickett T, 2015), HIV and substance abuse treatment interruption (Anis et al, 2002;Chan et al, 2004;Svikis, Pickens, Schweitzer, Johnson, & Haug, 1999), and related burdens on health, social and police services (Brunette, Kominsky, & Ruiz, 1991;Li et al, 2007;Pickett T, 2015;Riddell & Riddell, 2006;Shaner et al, 1995;Verheul et al, 1997;Zlotorzynska et al, 2014). While the aforementioned studies used predominantly administrative data, studies examining the drug use-income relationship that directly account for drug use are rare.…”
Section: Introductionmentioning
confidence: 99%